2017
DOI: 10.1016/j.diabres.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid and diabetes risk among Chinese women with a history of gestational diabetes mellitus

Abstract: Aims To assess the association of uric acid (UA) with the risks of postpartum type 2 diabetes and prediabetes among women with prior gestational diabetes mellitus (GDM). Methods We performed a cross-sectional study of 1262 GDM women at 1–5 years after delivery using the baseline data from the Tianjin Gestational Diabetes Mellitus Prevention Program. Logistic regression models were used to estimate the association of different levels of serum UA with the risks of type 2 diabetes and prediabetes. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
4
0
3
Order By: Relevance
“…In terms of gestational diabetes, Leng [56] found that the SUA level is positively related with the risk of T2DM and prediabetes in the Tianjin region of China gestational diabetes mellitus (GDM) prevention planning data. In the group with GDM and impaired glucose tolerance (IGT), the mean SUA level was significantly increased in early pregnancy, and a UA level of 3.95 mg/dl could predict GDM with 60% specificity and 100% sensitivity [57].…”
Section: Epidemiology Studiesmentioning
confidence: 99%
“…In terms of gestational diabetes, Leng [56] found that the SUA level is positively related with the risk of T2DM and prediabetes in the Tianjin region of China gestational diabetes mellitus (GDM) prevention planning data. In the group with GDM and impaired glucose tolerance (IGT), the mean SUA level was significantly increased in early pregnancy, and a UA level of 3.95 mg/dl could predict GDM with 60% specificity and 100% sensitivity [57].…”
Section: Epidemiology Studiesmentioning
confidence: 99%
“…Recently, Leng at al. [ 34 ] assessed the risks of postpartum T2DM and prediabetes development among Chinese women with previous GDM and found positive linear association of serum UA as a continuous variable with the risks of T2DM or prediabetes in cubic spline models and also increased multivariable-adjusted odds ratios for diabetes risk across quartiles of serum UA. Previously published studies on the relationship between UA and GDM did not take into account other metabolites in the UA pathway (such as X levels) as a possible marker of XOR activity; thus, our aims were (i) to determine mid-gestational and early postpartum UA and X levels and compare them between pregnant women with or without GDM, (ii) to analyze the relationship between mid-gestational and postpartum UA levels and parameters related to glucose intolerance (i.e., fasting plasma glucose (FPG) and oral glucose tolerance test (oGTT) values), (iii) to analyze the relationship between UA levels and selected markers of metabolic syndrome, (iv) to evaluate the effect of UA on perinatal outcomes, and (v) to study possible genetic contributions (i.e., genotype–phenotype relationships) to UA levels in pregnancy mediated by selected SNPs in genes encoding UA transporters ( ABCG2 rs2231142 and SLC2A9 rs1014290, rs12498742, rs16890979, and rs734553).…”
Section: Introductionmentioning
confidence: 99%
“…Faktor risiko DM tipe 2 yang disebabkan oleh pengaruh lingkungan telah dilaporkan oleh banyak peneliti. Dari hasil kajian sistematik ini diketahui bahwa paling tidak terdapat 9 kelompok faktor risiko DM tipe 2 dari faktor lingkungan, yaitu gangguan pada profil kimia darah (Guo et al, 2013;Sun et al, 2014;Akter et al, 2016;Leng et al, 2017;Lu et al, 2017;Urano et al, 2017;Yamaguchi et al, 2017;Choi et al, 2018;Shen et al, 2018), diet atau asupan zat nutrisi yang salah (Akter et al, 2017;Hong et al, 2017;Shan et al, 2018), gaya hidup (lifestlyle) yang buruk (Sakurai et al, 2013;Lou et al, 2015;, profil antrapometri yang bermasalah (Lim et al, 2013;Heianza et al, 2014;Wang et al, 2014;Cho et al, 2015;Chun et al, 2015;Xue et al, 2015;Lv et al, 2016;Zhang et al, 2016;Akter et al, 2017;Son et al, 2017;Yokomichi et al, 2017), kondisi gangguan/penyakit lain (Lee et al, 2013;Feng et al, 2014;Abraham et al, 2015;Akter et al, 2017;Subekti et al, 2017;Yamaguchi et al, 2017), gangguan sistem reproduksi (Yang et al, 2016;Wang et al, 2018), riwayat DM dalam keluarga (Vijayakumar et al, 2017), jenis pekerjaan sehari-hari (Gao et al, 2017), dan faktor risiko lain yaitu kondisi pendapatan dalam keluarga dan kondisi iklim saat lahir Si et al, 2017).…”
Section: Determinan Diabetes Melitus Tipe 2 Berdasarkan Faktor Lingkuunclassified
“…Asam urat merupakan produk oksidasi akhir pada metabolisme purin manusia dan biasanya digunakan sebagai indeks klinis untuk menilai fungsi ginjal dan asam urat (Leng et al, 2017). Dari hasil analisis ada hubungan positif antara serum asam urat dan risiko DM tipe 2 dan prediabetes pada postpartum 1 sampai 5 tahun di antara wanita China dengan riwayat DM gestasional yang dikaitkan dengan Indeks Massa Tubuh sebagai faktor risiko yang kuat untuk DM tipe 2 dan prediabetes.…”
Section: Determinan Diabetes Melitus Tipe 2 Berdasarkan Faktor Lingkuunclassified
See 1 more Smart Citation